Freqüência e fatores relacionados à disfagia orofaríngea após acidente vascular encefálico - Erica Oliveira Almeida (2009)
The frequency of dysphagia after stroke is different in various studies. Risk factors for dysphagia and the association between stroke and swallowing are also controversial in the literature. The objectives of the present study are to verify the frequency of oropharyngeal dysphagia in patients affected by stroke, to relate the type and degree of dysphagia with the subtypes of the disease and its pathophysiology and to observe the development of dysphagia during the hospitalization. Also compare non-dysphagic and dysphagic patients affected by stroke in relation to clinical and sociodemographic data. A cross-sectional study was performed including 100 patients who were admitted to the Betim Regional Public Hospital with stroke. The patients underwent clinical evaluation with speech therapy and clinical and sociodemographic data were collected from medical records. The stroke was classified according to type, location, and pathophysiology. Data from clinical evaluation of swallowing and the type, location, and pathophysiology of the lesion were correlated. GUSS scale was used for clinical evaluation of swallowing. OCSP and TOAST scales were used for classification of stroke. In the evaluation of swallowing, the frequency of dysphagia was 50%, suggesting an oral dysphagia for solid and pasty consistencies and pharyngeal dysphagia to liquid consistency. Most dysphagic patients (56%) showed severe dysphagia with high risk of aspiration. In the clinical evaluation performed at hospital discharge, we observed frequency of dysphagia in 37.9% of patients. 58.3% of dysphagic patients showed moderate dysphagia with risk of aspiration. Only a previous history of stroke showed a relationship with dysphagia (p = 0.022). No relationship was observed between the location and pathophysiology of stroke and dysphagia. This study shows high frequency of dysphagia after stroke and there are significant changes in the degree of dysphagia, in the profile of swallowing for each consistency and the possibility of feeding of patients during the hospitalization period.